Dinamika Kompetensi Absolut Antara Arbitrase & Kepailitan Penundaan Kewajiban Pembayaran Utang - Febry Arisandi (BANI Arbitration and Law Journal, 2025)
Abstrak In the Indonesian legal system, arbitration and bankruptcy are two different mechanisms for dispute resolution, but they are closely related in terms of the competence of the adjudicators to resolve rights and obligations. The competence of adjudication in arbitration and bankruptcy has complex dynamics, particularly in terms of determining jurisdiction, submission procedures, and understanding of applicable law. This article discusses the dynamics of adjudication competence in arbitration and bankruptcy in Indonesia based on decisions related to bankruptcy and suspension of debt payment obligations. In terms of jurisdiction, the court has exclusive jurisdiction in bankruptcy cases, while arbitrators require the agreement of the parties in dispute to resolve disputes through arbitration. However, in practice, Commercial Court judges in bankruptcy and suspension of debt payment obligations (PKPU) cases in Indonesia still make decisions on disputes that contain arbitration clauses in their business agreements. In conclusion, the dynamics of adjudicating competence in arbitration and bankruptcy in Indonesia require clear and consistent regulations for legal certainty in doing business in Indonesia. Commercial Court judges must have adequate knowledge about arbitration and related arbitration rules and agreements and be able to make fair and accurate decisions in resolving disputes. In the long run, efforts to improve adjudication competence are expected to increase public trust in the Indonesian legal system.